Perbandingan Efektivitas TiO2 dan ZnO pada Resin Immobilized Photocatalyst Technology (RIPT) dalam Menyisihkan BOD pada Limbah Tahu - Euis Nurul Hidayah; Dinda Ayu Lavyatra (Prosiding ESEC, 2022)
Liquid waste generated from tofu processing has a high BOD content. Therefore, it is necessary to innovate wastewater treatment for the tofu industry so as not to cause a decrease in the environmental carrying capacity of the waters. This research uses Resin Immobillized Photocatalyst Technology (RIPT) which is expected to create new innovations for the community and can be applied to the WWTP tofu industry or other industries. Results Based on the research, the higher the dose of Resin Immobillized Photocatalyst (RIP) added, the more organic compounds decomposed. The best results of the removal of BOD parameters in RIP-TiO2 in a dose of 15gram the percentage of BOD removal reached 79.95%, while RIP-ZnO in the same dose of 15gram the proportion of removal reached 90.20%. The selection of sampling times of 0, 30, 60, 120 and 180 which resulted in the maximum percentage of BOD removal was a sampling time of 180 minutes. This can happen because the longer the wastewater is exposed to RIP, the more ion exchange occurs.